Entanglements of media and space: an exploratory case study of two public arts projects in Johannesburg and Cape Town - Brown, Storm Jade (Centre for Film and Media Studies, 2025)
This research presents a spatially and media sensitive analysis of the layers of discourse created by two South African public art case studies between 2017 and 2019. Public art is selected as the research object as it “necessarily explores the very meaning of public space” (Wacławek, 2011:65) and it “can become the central focus for a range of competing discourses related to that domain” (Clements, 2008:19). Furthermore, the concept of public space has changed since the “internet and related technologies have created a new public space for politically oriented conversation…” (Papacharisi, 2002:9). When public art is photographed and re-presented in an online space, its surrounding audience and public sphere also extends. This results in a collapse of physical spaces into online ones, and has transformed contemporary understandings of what it means to be public and what it means to be visible. The emplaced yet fragmented nature of public art could not be more relevant for a South African context where public spaces are increasingly contested in a post-apartheid context. Therefore two specific public art case studies were chosen for this research. These projects first appeared in physical locations before moving into online and mediated spaces. The first project, #ArtMyJozi by The Trinity Sessions, features community public art projects created in and around the Rea Vaya Bus Rapid Transit Terminals on Louis Botha Avenue in Johannesburg. #ArtMyJozi was commissioned by the City of Johannesburg and the Johannesburg Development Agency. It used a placemaking approach to guide the artwork creation process and community engagement. The second case study looks at three iterations of BAZ-ART's International Public Art Festival (IPAF) from its inaugural year in 2017. The IPAF started off as a South African iteration of a global public art festival, and was a commercially sponsored three-day long event where various murals were created in and around Salt River and the surrounding Central Business District of Cape Town. Although both projects are loosely branded as ‘public art', each project underwent a very different project delivery and community inclusion process. Furthermore, there was no shared meaning about the term public space. These differences in approach and process resulted in vastly different public responses and discourse themes for each case study. This discourse emerged in both online news media and Social Network Sites, as well as within the physical spaces that the works occupied. Therefore, in order to study both sites of discourse for each public art case study, this research uses an exploratory case study approach. The approach triangulates various data collection sources including field visits, social media posts, press releases, government policies and interviews. After this, a Critical Discourse Analysis and a Content Analysis are used to discern key interrelated discourse themes. This layered and triangulated approach is informed by Couldry and McCarthy's (2004) conceptual framework of MediaSpace. MediaSpace presents a spatially sensitive approach to examining media objects and the discourse that they create over five distinct levels. Importantly, it highlights how each level is interconnected with all other levels. It also considers the cumulative scale of effects between media and space. This study is a necessary one, as it explores how discourse is created in public art projects in South Africa, and by extension, how discourse around public spaces is amplified, maintained or negated in various spaces including online ones. There has not yet been a localised and digitally inclusive study of this phenomenon in South Africa.